Anwar Ibrahim: A Pursuit for Global Justice and Peace through Dialogue (Yusmadi Yusoff) - Mohd Shazani, Masri (ISTAC-IIUM, 2024)
Yusmadi Yusoff presents a fascinating picture of a visionary leader in his latest book, Anwar Ibrahim: A Pursuit for Global Justice and Peace via Dialogue. Drawing on his lengthy history of political and personal interaction with the present Malaysian Prime Minister BOOK REVIEWS 446 Anwar Ibrahim, Yusmadi tells a story that goes beyond the political and exposes a man fervent in his ability to bridge divisions through dialogue. This book narrates Anwar’s story from his student days as an activist, then through the ups and downs of his political career, until his present position as a world-renowned Muslim statesman currently ranked as the 15th most influential Muslim figure in the world according to “The World’s Most Influential Muslims (2025)” by RISSC. It showcases Anwar’s resoluteness in upholding justice, peace, and harmony despite increasing division nationally and internationally.